2012
DOI: 10.5402/2012/684981
|View full text |Cite
|
Sign up to set email alerts
|

Alternate-Fueled Combustor-Sector Performance—Part A: Combustor Performance and Part B: Combustor Emissions

Abstract: Alternate aviation fuels for military or commercial use are required to satisfy MIL-DTL-83133F or ASTM D 7566 standards, respectively, and are classified as "drop-in" fuel replacements. To satisfy legacy issues, blends to 50% alternate fuel with petroleum fuels are acceptable. Adherence to alternate fuels and fuel blends requires "smart fueling systems" or advanced fuel-flexible systems, including combustors and engines, without significant sacrifice in performance or emissions requirements. This paper provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…While the lean blowout tests of [58,68] showed no significant differences between the tested alternative jet fuels and conventional ones, the results of [59] demonstrated a better LBO performance for the tested FT CTL than RP-3 at low liner pressure drop conditions, which could be caused by the different fuel distillation curves as suggested by the authors. Burger et al [69] has systematically studied the lean blowout behavior of Sasol FSJF ® , SPK, Jet A-1, and other fuel blends in a heterogeneous laboratory combustor.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…While the lean blowout tests of [58,68] showed no significant differences between the tested alternative jet fuels and conventional ones, the results of [59] demonstrated a better LBO performance for the tested FT CTL than RP-3 at low liner pressure drop conditions, which could be caused by the different fuel distillation curves as suggested by the authors. Burger et al [69] has systematically studied the lean blowout behavior of Sasol FSJF ® , SPK, Jet A-1, and other fuel blends in a heterogeneous laboratory combustor.…”
mentioning
confidence: 82%
“…The results of [65] showed that CO emission index for SPK was higher than that for Jet A-1 in the leaner conditions and was lower in the richer conditions; and NO x emission index for SPK was lower than that for Jet A-1 in all the tested conditions, except for rich conditions at high inlet air temperatures. Shouse et al [68] compared the emissions of a FT GTL with those of JP-8 and found that CO emission of GTL was lower than that of JP-8 for all the tested F/A, while NO x emission of GTL was lower than that of JP-8 at leaner conditions, but higher at richer conditions. Other tests of [59,71] showed no significant differences in CO and NO x emissions between the tested alternative and conventional jet fuels.…”
mentioning
confidence: 99%
See 1 more Smart Citation